Mindfulness, Buddhism, and Rogerian Argument - Alexandria Peary (Journal of the Assembly for Expanded Perspectives on Learning, 2005)
Use of Buddhist mindfulness practices with Rogerian argument highlights Roger’s ideas of empathy and conscious listening which help develop a rhetorical imagination in the student.